2016
DOI: 10.1016/j.adolescence.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Changes in parent–adolescent joint activities between 2002 and 2014 in the Czech Republic, Health Behaviour in School‐aged Children (HBSC) study

Abstract: Joint family activities (JFA) are linked to healthy adolescent development. The aim of the present study is to report time trends in JFA between 2002 and 2014. The sample concerned 16 396 adolescents aged 11, 13, and 15 years (48.4% boys) from the 2002, 2006, 2010, and 2014 surveys of the Health Behaviour in School-aged Children (HBSC) study in the Czech Republic. The overall changes in JFA were evaluated using logistic regression. Compared with 2002, there was a slight increase in four out of the six selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…Eating a meal together and sitting and talking about things together are among the most frequent joint activities, while playing sports together and playing indoor games together are the less frequent activities, what was confirmed also in the study of Zaborskis et al [65]. In the study of Vokacova et al [66] reported time trends in joint family activities between 2002 and 2014. Compared with 2002, there was a slight increase in four out of the six selected joint family activities (watching TV or a video, playing indoor games, eating meals, going for a walk, going places, visiting friends or relatives, playing sports, sitting and chatting).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Eating a meal together and sitting and talking about things together are among the most frequent joint activities, while playing sports together and playing indoor games together are the less frequent activities, what was confirmed also in the study of Zaborskis et al [65]. In the study of Vokacova et al [66] reported time trends in joint family activities between 2002 and 2014. Compared with 2002, there was a slight increase in four out of the six selected joint family activities (watching TV or a video, playing indoor games, eating meals, going for a walk, going places, visiting friends or relatives, playing sports, sitting and chatting).…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, families did not eat together as often as in 2002, which might have negative consequences for healthy adolescent development. Also, adolescents aged 11 got involved in joint family activities more than their older counterparts [66].…”
Section: Discussionmentioning
confidence: 99%
“…Youth tend to spend more time with peers and start to form cliques (Gifford‐Smith & Brownell, 2003; Larson & Verma, 1999). This happens at the expense of shared family time, which becomes rarer with increasing age (Vokacova, Badura, Pavelka, Kalman, & Hanus, 2016; Zaborskis, Zemaitiene, Borup, Kuntsche, & Moreno, 2007). Consequently, parental control and knowledge about their children's friends and activities decreases, and adolescents might disclose less to their parents (Keijsers & Poulin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Especially girls tend to experience more difficulties in talking with their fathers, both biological and stepfathers (24,30). This may be associated with the overall higher frequency and quality of time spent by boys with their family, especially with their fathers (16,31). Girls, in contrast, experience greater limitations on their freedom and higher levels of parental monitoring (16,32).…”
Section: Gender and Age Differencesmentioning
confidence: 99%